Coexistence of tmexCD-toprJ, blaNDM-1, and blaPME-1 in multi-drug-resistant Pseudomonas juntendi isolates recovered from stool samples - Wugao Liu; Yi Liu; Jing Jin; Ningjun Wu; Weiping Wu; Chunsheng Qu (Microbiology Spectrum)
ABSTRACT Pseudomonas juntendi has received limited research attention, yet strains carrying multi-drug resistance genes pose a threat to global public health. We aimed to characterize the genome of two fecal-derived strains of Pseudomonas juntendi, both harboring tmexCD-toprJ, blaNDM-1, and blaPME-1 on the chromosome, recovered from two patients. Average nucleotide identity (ANI) analysis showed that L4008hy and L4046hy were remarkably similar. They showed high levels of resistance to aztreonam, imipenem, ciprofloxacin, amikacin, piperacillin–tazobactam, ceftazidime–avibactam, and polymyxin B in antimicrobial susceptibility testing using agar dilution method and broth microdilution methods. Additionally, an integrative and conjugative element (ICE) similar to ICE6660 was detected on the chromosome, which contains all resistance genes and has a relatively complete transfer module, and potential transfer mechanisms were identified. Phylogenetic analysis of P. juntendi reveals the genomic diversity of the species and sheds light on environmental–human transmission.IMPORTANCEUp to now, research on Pseudomonas juntendi is still very limited. Our findings suggest that P. juntendi commonly carries diversity resistance genes on chromosomes and is stably inherited, highlighting the need for further studies on the antimicrobial properties of this bacterium. The coexistence of tmexCD-toprJ, blaNDM-1, and blaPME-1 on the chromosome in P. juntendi was reported for the first time. The identified integrative and conjugative element (ICE) contains all the identified resistance genes and serves as a vector for resistance gene transfer between bacteria. P. juntendi, which harbors multi-drug resistance genes, particularly those encoding carbapenemases, acts as a reservoir of resistance genes. Its spread in clinical settings poses additional challenges to treatment.